Faculty Teaching Improvement: Opportunities Within a Graduate Student & Faculty Community of Practice - Jeremy Elliott-Engel; Donna Westfall-Rudd (Adult Education Research Conference, 2018)
Improving higher-education teaching is a growing focus on American colleges. A program was developed to train current PhD students in effective pedagogy practices. The Community of Practice resulted in current teaching faculty pedagogical improvement.
Keywords: Community of Practice (CoP); college teaching; professional development; Qualitative methodology